Islamic Educational Values Contained In The Wedding Tradition Of The Sambas Malay Community - Ilham; Syahruddin Usman; Baharuddin; Purniadi Putra (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The purpose of this research is to analyze the values of Islamic education contained in the marriage tradition of the Sambas Malay community. This research uses a qualitative approach. The approach used in this research is a phenomenological approach. Data collection techniques with observation, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and conclusion drawing. Primary data sources were obtained from cultural leaders, and religious leaders as key informants and several village heads and elements of implementing marriage activities. While secondary data is obtained from books, journals, and websites. The results showed that the wedding tradition of Sambas Malay community is based on the philosophy of "adat bersandikan syara' and syara' bersandikan kitabullah". The implementation of the wedding tradition is an enculturation entity of Islamic values that are actualized in the form of brotherhood value (ukhuwah), honesty value and right promise (al-wafa), cooperation value, responsibility value, loyalty value, balance value (al-adalah), peace value, equal position value, justice value, (al-musawwah), and harmony value. The educational values contained in the marriage tradition of the Sambas Malay community can be classified as follows, namely Ta'aruf, ta'awun deliberation, advice, Mu'asyarah, Ba'ah (ability) and Mitsaqan ghalizhan